1992
DOI: 10.1038/hdy.1992.102
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal differentiation in colonizing populations of Ceratitis capitata

Abstract: Two ancestral populations (Kenya and Reunion), two Mediterranean (Procida and Sardinia) and one new American population (Guatemala) of Ceratitis capitata were examined by electrophoresis for genetic variability at 27 enzyme loci. Two ordination approaches (principal component analysis and a tree representation) and F-statistical analysis have been used to distinguish the various patterns of genetic variations and to infer the underline causes and their relative contribution to the total variation. Three main p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0
9

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 8 publications
7
41
0
9
Order By: Relevance
“…Several factors may contribute to the successful and wide-spread establishment of C. capitata here and elsewhere. Amongst these are the species’ polyphagous life-history [6], [11], short development time, and high population reproductive potential [12]. Ceratitis capitata may also have a broader climate niche compared to its congeners [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors may contribute to the successful and wide-spread establishment of C. capitata here and elsewhere. Amongst these are the species’ polyphagous life-history [6], [11], short development time, and high population reproductive potential [12]. Ceratitis capitata may also have a broader climate niche compared to its congeners [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this work is to confirm and to extend the previously established knowledge on the genetic structure and differentiation of medfly populations (Gasperi ci ai., 1991;Malacrida et al, 1992). In C. capitata, RAPDs reveal a surprisingly high level of hidden genetic variability mainly in wild African populations, which decreases in the peripheral ones to levels similar to those observed in some laboratory colonies.…”
Section: Introductionmentioning
confidence: 99%
“…Allozymes have proved the existence of nonrandom distributions of genetic variability in geographical populations of C. capitata: spatial and temporal differentiations characterize this species after its spread from the putative source area to the periphery of its present geographical range Malacrida et al, 1992). With respect to the colonization patterns, it has been suggested that the medfly populations, like those of Drosophila melanogaster (David & Capy, 1988), can be divided into three main categories: ancestral, ancient and new populations from sub-Saharan Africa, the Mediterranean basin, and the New World, respectively (Malacrida etal., 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For each of these biochemical loci, the electrophoretic banding patterns of C. capitata were used as a standard because electrophoretic variation in this species is well documented (Gasperi et al, 1991;Malacrida et a!., 1992;Baruffi eta!., 1995).…”
Section: Species Samplesmentioning
confidence: 99%
“…In this context, Rhagoletis flies (R. pomonella species complex) have been at the centre of a discussion on sympatric speciation (Bush, 1966(Bush, , 1969Feder et a!., 1988Feder et a!., , 1990. Electrophoretic studies of genetic differentiation have provided a powerful tool for the analysis of sympatric speciation and phylogeny in Rhagoletis (Berlocher & Bush, 1982;Berlocher et a!., 1993), for resolving species complexes in the A. fraterculus group (Malavasi & Morgante, 1983;Steck, 1991) and in population genetic analysis in C. capitata (Gasperi et a!., 1991;Malacrida et al, 1992;Baruffi et aL, 1995). All of these studies suggest the great potential of genetic approaches for biogeographical and phylogenetic analysis of Tephritidae flies.…”
Section: Introductionmentioning
confidence: 99%